THE INFLUENCE OF AUDITOR’S COMPETENCE AND ORGANIZATIONAL COMMITMENT TO THE IMPLEMENTATION OF FINACIAL STATEMENT REVIEW IN ACEH INSPECTORATE - Amirullah Amirullah; Darwanis Darwanis; M. Rizal Yahya (Program Magister Akuntansi Unsyiah, 2010)
This research is aimed at analizing the infulence of auditor’s compentence and organizational commitment to implementation of finacial statement review both simultaneously and partially.Serving as the population in this research are 48 qualified auditor respondents from Aceh Inspectorate. The data-collection was conducted by questionaire share-out, and the test of its validity and reliability. The product moment correlation was used in validity test with 0,05 significance rate while in reability test Cronbach Alpha formula wa used.The result of the research shows that there is influence from auditor’s competence and organizational commitment to the implementation of finacial statement review both simultaneously and partially. Determination Coefficient (R2) was 0,740. Its mean as much as 74.0% of changes in implemention of financial statement review can be explained by changes in auditors’s competence and commitment organizatinal factors. The rest 26.0 % can be explained by the other variables outside this research. The variable of auditor’s competence positifly influences to the implementation of financial statement review as much as 21,0 % and so does organizational cmmitment as much as 16,0%. keywords : auditor’s compentence, organizational commitment and implementation of finacial statement review